FGF10 Enhances Peripheral Nerve Regeneration via the Preactivation of the PI3K/Akt Signaling-Mediated Antioxidant Response - Dong, Lvpeng; Li, Rui; Li, Duohui; Wang, Beini; Lu, Yingfeng; Li, Peifeng; Yu, Fangzheng; Jin, Yonglong; Ni, Xiao; Wu, Yanqing; Yang, Shengnan; Lv, Guanxi; et al. (Frontiers in Pharmacology, 2019)
The process of axonal regeneration after peripheral nerve injury (PNI) is slow and mostly incomplete. Previous studies have investigated the neuroprotective effects of fibroblast growth factor 10 (FGF10) against spinal cord injury and cerebral ischemia brain injury. However, the role of FGF10 in peripheral nerve regeneration remains unknown. In this study, we aimed to investigate the underlying therapeutic effects of FGF10 on nerve regeneration and functional recovery after PNI and to explore the associated mechanism. Our results showed that FGF10 administration promoted axonal regeneration and functional recovery after nerve damage. Moreover, exogenous FGF10 treatment also prevented SCs from excessive oxidative stress-induced apoptosis, which was probably related to the activation of phosphatidylinositol-3 kinase/protein kinase B (PI3K/Akt) signaling. The inhibition of the PI3K/Akt pathway by the specific inhibitor LY294002 partially reversed the therapeutic effects of FGF10 both in vivo and in vitro. Thus, from our perspective, FGF10 may be a promising therapeutic drug for repairing sciatic nerve damage through countering excessive oxidative stress-induced SC apoptosis.